A job demands-resources approach to presenteeism. Issue 4 (8th August 2016) - McGregor, Alisha; Magee, Christopher A.; Caputi, Peter; Iverson, Donald
Abstract : Purpose: Utilising the job demands-resources (JD-R) model, the purpose of this paper is to examine how aspects of the psychosocial work environment (namely, job demands and resources) are associated with presenteeism, and in particular, whether they are indirectly related via burnout and work engagement. Design/methodology/approach: A cross-sectional survey of 980 working Australians measured the relationships between job demands (i.e. workplace bullying, time pressure and work-family conflict), resources (i.e. leadership and social support), burnout, work engagement and presenteeism. Path analysis was used to test the proposed hypotheses whilst controlling for participant demographics (i.e. sex, age, work level, duration and education). Findings: Higher job demands (workplace bullying, time pressure, and work-family conflict) and lower job resources (leadership only) were found to be indirectly related to presenteeism via increased burnout. While increased job resources (leadership and social support) were indirectly related to presenteeism via improved work engagement. Practical implications: The findings are consistent with the JD-R model, and suggest that presenteeism may arise from the strain and burnout associated with overcoming excessive job demands as well as the reduced work engagement and higher burnout provoked by a lack of resources in the workplace. Intervention programmes could therefore focus on teaching employees how to better manage job demands as well as promoting the resources available at work as an innovative way to address the issue of rising presenteeism. Originality/value: This study is important as it is one of the first to examine the theoretical underpinnings of the relationship between presenteeism and its antecedents.